Accessibility evaluation of COVID-19 vaccine registration websites across the United States. (16th May 2021) - Alismail, Sarah; Chipidza, Wallace
Abstract: This exploratory study investigated the web accessibility of 54 official COVID-19 vaccine registration websites in the US and their concordance with the WCAG 2.0 and 2.1 guidelines. We employed AChecker, WAVE, and SortSite web accessibility evaluation tools to conduct automated analyses of these websites. The results showed suboptimal compliance with WCAG 2.0 and 2.1 guidelines, as determined using the AChecker, WAVE, and SortSite tools. These shortcomings in compliance may pose difficulties to users with disabilities as they access information on the websites. Based on our findings, we offered recommendations for states and other authorities to improve the accessibility of their websites to ensure that users with disabilities can independently schedule vaccination appointments.